ASSESSING SOIL EROSION SEVERITY IN TEMPORAL AND SPATIAL PATTERN: A CASE STUDY IN THE PLEIKU PLATEAU, GIA LAI PROVINCE - Thanh Tuan, Nguyen; Quoc Tuan, Do; Thuy Chi, Tran (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Soil erosion is one of the major causes of land degradation and negatively impacts the soil environment in the world. There are two approaches to assessing soil erosion severity (SES) in terms of the decline of soil productivity in a given area: (1) classifying actual soil loss according to erosion risk classes, and (2) comparing actual soil loss to soil loss tolerance to classify erosion severity. This paper aims to explore changes in SES during 2005–2015 in the Pleiku Plateau, Gia Lai province, Vietnam, as a case study for comparing the two approaches. Regarding actual soil erosion, the average soil erosion rate declined by 0.16 ton/ha/year in the plateau terrain and increased by 0.02 ton/ha/year in the mountain relief. During 2005-2015, the low erosion risk area decreased by 6,302 ha, while the remaining erosion risk classes increased. With respect to soil erosion severity, the tolerable and moderate soil erosion acreages reduced by about 671.8 ha and 2,266.7 ha, respectively, and the high and severe ones increased; however, the severe soil erosion areas grew drastically. The differences between the two approaches come from consideration of the soil loss tolerance in assessing soil erosion severity. Thus, in order to assess SES for a region, comparing actual soil loss to soil loss tolerance provides SES indices that reflect the soil erosion problem, rather than only classifying actual soil loss. The findings are of enormous significance for environmental management, especially in addressing soil degradation.